The flawed evangelist (John) Mark - Kok, Michael (2012)
Due to the popularity of the name Marcus, C. Clifton Black has argued that there is no necessary identity between the John Mark of the book of Acts (12:12, 25; 13:5, 13; 15:37-39) with the Mark(s) found in the Pauline corpus (Col 4:10; Phlm 24; 2 Tim 4:11), the first epistle of Peter (1 Pet 5:13) or the writings of Papias of Hierapolis (cf. Eusebius, Hist. eccl. 3.39.15). On the contrary, this paper will propose that the author of Luke-Acts was not only aware of Mark's connection with Paul and Barnabas, but also critically interacted with the developing traditions about the evangelist Mark. The positive and negative aspects of the literary characterization of John Mark may be a clue to the ambivalent reception of Mark's gospel in Luke-Acts.